Walking out [videorecording (DVD)] - Smith, Alex, approximately 1967-; Smith, Alex, approximately 1967-; Smith, Andrew, approximately 1967-; Smith, Andrew, approximately 1967-; Bomer, Matthew, 1977-; Wiggins, Josh; Pullman, Bill; Quammen, David, 1948- (Shout! Factory, 2018)
When a father-son hunting trip goes awry leaving the father critically wounded, it is up to his teenage son to find a way for them to survive.